Sino-African Relations: Emerging Concerns and Dynamics (Journal of International Studies, 2020)
The objective of this article is to demonstrate that one of the most significant consequences of the growth of China-Africa relations is the positioning of the African continent as a possible theatre for US-China geo-political rivalry. The interpretative approach adopted in this essay involves a comprehensive review of extant literature, and draws on recent data to highlight China’s economic forays into Africa and the attendant implications. Undeniably, Africa’s strategic minerals are of great value to both competing global powers, that is, the United States and China. Interestingly, China’s presence in Africa has been bolstered by its state-capitalist model which has captivated and convinced most African leaders into believing that this alternative development paradigm might be the answer to Africa’s long quest for economic growth. To many African leaders whose regimes are mainly pseudo-democracies, the Chinese model which delivers economic growth without embracing democracy has become an attractive option vis-à-vis the Western model which is predicated on unpopular conditionalities of good governance and respect for human rights. While the emergence of China in Africa has been welcomed in the continent, it is equally true that some concerns and fears are emerging over the growing presence of China in Africa. Some of these concerns include the reversal of the democratization agenda in some African countries; the unequal trade relations between Africa and China; environmental questions on Chinese investments; and fears of a re-packaged form of new colonialism.More importantly, most African countries are apprehensive about the growing tensions between China and the US over Africa which might lead to a new ‘Scramble for Africa’ and the re-emergence of proxy conflicts on the continent.